Mediating Role of Family Problems in the Academics of Learners: Basis for Community Education Seminar - Bernal Jr., Hernando L.; Gumaru, Renz Chester R.; Go, Bernie B. (RIRAI Publisher, 2024)
This study examines the relationship between family dynamics and the academic performance of first-year nursing students. It explores the role of family support, criticism, and emotional support in shaping students’ academic outcomes and overall well-being. By assessing the mediating effects of family dynamics, the study aims to identify factors that foster resilience and coping mechanisms in students facing academic challenges. Insights gathered will inform strategies to improve family relationships and institutional support systems. The study also proposes an educational seminar plan to raise community awareness about the critical role of family in student success, promoting holistic development and academic excellence.